Balance 2011 - Sarmiento, Eduardo (Diario El Espectador, 2011)
El producto nacional avanzó más de 5% en los últimos tres trimestres, se debilitó en el cuarto y en 2012 crecerá 4,5%. El desempleo descendió un punto porcentual, pero no está representado en ocupaciones de calidad. Los proyectos sociales presentados al Congreso no rindieron los frutos previstos.

The national product advanced more than 5% in the last three quarters, weakened in the fourth and in 2012 it will grow 4.5%. Unemployment fell one percentage point, but it is not represented in quality occupations. The social projects presented to Congress did not yield the expected results.
Keywords: Economía - Colombia; Política económica - Colombia; Colombia - Aspectos socioeconómicos; Economy - Colombia; Economic policy - Colombia; Colombia - Socioeconomic aspects